Telegram Chatbot as DASH Diet Education Media for Employees - Salsabila, Annisa; Wirawan, Susilo; Sitasari, Almira (Window of Health : Jurnal Kesehatan, 2024)
Hypertension and prehypertension are a unity of diseases caused by various risk factors that can be experienced by employees. A diet known for patients who have high blood pressure is the DASH diet with one of the efforts to prevent the incidence of hypertension is through education. Research objectives: Determine the effect of providing nutrition education through Telegram Chatbot on increasing knowledge of the DASH diet in employees with hypertension. This type of research is Quasi Experimental research. Pre-test and post-test research design with control group design. Results of study, the number of male respondents was more, namely 18 people (58%), compared to female respondents, as many as 13 people (42%). The average post-test score was greater at 92.12, while the pre-test was 70.61. The difference between the average pre-test and post-test was 21.51. The results of the t-test analysis obtained a p-value of 0.000 (less than 0.05). Conclusions: There is an influence of Telegram Chatbot media on changes in DASH dietary knowledge in employees with hypertension in Padukuhan Purbosari.